ChemInform Abstract: Recent Advances in the Development of Synthetic Chemical Probes for Glycosidase Enzymes. Issue 33 (August 2015) - Burke, Helen M.; Gunnlaugsson, Thorfinnur; Scanlan, Eoin M.
Abstract Review: 168 refs.